Cochlostoma Jan, 1830 revised: an overview of the subgenus Turritus Westerlund, 1883 and its species (Caenogastropoda, Cochlostomatidae) - Zallot, Enrico; Kamchev, Panche; Schilthuizen, Menno; Fehér, Zoltán; De Mattia, Willy; Gittenberger, Edmund (European Journal of Taxonomy, 2024)
The taxa of the subgenus Turritus of Cochlostoma (Cochlostomatidae) are analysed based on molecular and morphological data. The phylogenetic trees, based on ribosomal (16S) and nuclear (H3) DNA, indicate that the currently accepted taxonomy should be revised. Based on our data, there are 37 species in Turritus of which 5 are new to science: Cochlostoma (Turritus) pallgergelyi sp. nov., C. (T. ) muranyii sp. nov., C. (T. ) hallgassi sp. nov., C. (T. ) kontschani sp. nov. and C. (T. ) lacazei sp. nov. Of these, we describe the shells and the female genitalia and summarize the distributional data. Some samples (or set of samples) will remain undetermined for lack of data and these are reported in the appendix.